FRAMEWORK FOR EVALUATING LATERAL RESISTANCE OF DIAGRID WITH BASE COLUMN (Malaysian Journal of Civil Engineering, 2018)
Development in highrise building construction had lead to the emergence of diagrid system which currently has gained popularity among the designers. Diagrid which is a portmanteau of diagonal grid is a framework of diagonally intersecting members at the exterior of a structure that lends to high structural efficiency in terms of resisting gravity and lateral loads, resulting in less steel consumption. The new aesthetic appearance of the diagrid has triggered the new interest in architecture. However, most structures of diagrid systems had been designed with full triangulated members from the ground level to the top of the buildings which cause a limited interior room at the ground level and limited spacing for entrance. The usage of vertical columns at ground level that are connected to diagrid members at the upper floor is an alternative to increase both interior room and spacing for entrance at ground level. This raises the question on the efficiency of this type of diagrid system in resisting the lateral load. Thus, a review on the framework is carried out to study the efficiency of this type of diagrid system in reducing the lateral displacement both statically and dynamically.